2009
DOI: 10.1097/ta.0b013e31819ce457
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expanding Hemostatic Polymer for Control of Exsanguinating Extremity Bleeding

Abstract: SEHP is a novel, light, and portable material to control EEI effectively. It does not require another person for compression nor does it compromise the circulation. As EEI occurs with alarming frequency in the battlefield, SEHP may not only present an optimal hemostatic method for military applications but also be useful in the civilian prehospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…It is presently believed that the method described may be more efficient than that used in the present study, as more diffuse and stable pressure could be transferred to the bleeding site. [8,15] Few studies concerning hemostatic effect of chitosan have been reported. Hamid et al [21] conducted a study with Persian Gulf Chitosan (PGC) in a carotid puncture hole sheep model, and the results suggested that PGC was safe and effective means of achieving hemostasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is presently believed that the method described may be more efficient than that used in the present study, as more diffuse and stable pressure could be transferred to the bleeding site. [8,15] Few studies concerning hemostatic effect of chitosan have been reported. Hamid et al [21] conducted a study with Persian Gulf Chitosan (PGC) in a carotid puncture hole sheep model, and the results suggested that PGC was safe and effective means of achieving hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3,7,[18][19][20] While many local hemostatic agents have been tested, no clear consensus exists regarding optimal hemorrhage control strategy for external bleeding. [1,4,8,9,[13][14][15][16][17]20,[24][25][26][27][28][29][30] However, Pusateri and Grissom [10,19] outlined ideal qualities of hemostatic agents for prehospital and battlefield use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On packing into a wound it controls bleeding by expanding to exert a pressure on the wound surface and by absorbing the "aqueous phase" of blood, concentrating clotting factors locally [36]. SEHP appears to absorb water in a non-exothermic reaction.…”
Section: Sehpmentioning
confidence: 99%